Committed to work but vulnerable: self‐perceptions and mental health in NEET 18‐year olds from a contemporary British cohort. (26th August 2015) - Goldman‐Mellor, Sidra; Caspi, Avshalom; Arseneault, Louise; Ajala, Nifemi; Ambler, Antony; Danese, Andrea; Fisher, Helen; Hucker, Abigail; Odgers, Candice; Williams, Teresa; Wong, Chloe; Moffitt, Terrie E.
Abstract : Background: Labour market disengagement among youths has lasting negative economic and social consequences, yet is poorly understood. We compared four types of work‐related self‐perceptions, as well as vulnerability to mental health and substance abuse problems, among youths not in education, employment or training (NEET) and among their peers. Methods: Participants were from the Environmental Risk (E‐Risk) longitudinal study, a nationally representative UK cohort of 2, 232 twins born in 1994–1995. We measured commitment to work, job‐search effort, professional/technical skills, 'soft' skills (e.g. teamwork, decision‐making, communication), optimism about getting ahead, and mental health and substance use disorders at age 18. We also examined childhood mental health. Results: At age 18, 11.6% of participants were NEET. NEET participants reported themselves as committed to work and searching for jobs with greater diligence than their non‐NEET peers. However, they reported fewer 'soft' skills (B = −0.98, p < .001) and felt less optimistic about their likelihood of getting ahead in life (B = −2.41, p < .001). NEET youths also had higher rates of concurrent mental health and substance abuse problems, but these did not explain the relationship with work‐related self‐perceptions. Nearly 60% of NEET (vs. 35% of non‐NEET) youths had already experienced ≥1 mental health problem in childhood/adolescence. Associations of NEET status with concurrent mental health problems were independent of pre‐existing mental health vulnerability. Conclusions: Our findings indicate that while NEET is clearly an economic and mental health issue, it does not appear to be a motivation issue. Alongside skills, work‐related self‐perceptions and mental health problems may be targets for intervention and service provision among this high‐risk population.